History in Senior Secondary School CAPS 2012 and beyond: A comment (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
History Education has been a neglected aspect of the great educational debate in South Africa in recent times. Despite its high pro!le in anti - apartheideducation the subject has not received the same attention as science and maths in the post 1994 debates, and was to a large extent sidelined by Curriculum2005 and OBE reforms because of the emphasis on constructivist notions of knowledge which devalued formal historical learning. Although partially rescued by Asmal’s reforms in the Revised National Curriculum Statement (RNCS) of 2002, it has taken the CAPS curriculum of 2010-2011 to put it back at the centre of the educational picture by recognising the importance of history as a key aspect of the worthwhile knowledge to be offered at school. This article looks at the new CAPS curriculum for senior school (Grades 10-12) and recognises its value but also turns a critical eye to question the credibilityof the new curriculum in terms of knowledge criteria and pedagogic viability.
Keywords: History Education; Curriculum development; South Africa; Historiography; Teacher knowledge; Pedagogy; CAPS